The relation between engagement quality control review hours and auditor changes: evidence from South Korea - Song, Jae-Won; Kim, Yong-Shik (Journal of Business Economics and Management, 2021)
The purpose of this study is to analyze whether engagement quality control review (EQCR) hours affect auditor changes and whether abnormal audit fees and changes in management have moderating effects on the relation between EQCR hours and auditor changes. The logit regression model is designed to investigate the relation between EQCR hours and auditor changes. The study finds evidence that EQCR hours are higher before auditors are changed. It also documents that abnormal audit fees weaken and that changes in management strengthen the positive relation between EQCR hours and auditor changes. In summary, high EQCR hours increase the probability of auditor changes, and the results imply that EQCR hours are a proxy for the audit risk perceived by auditors. This research is the first empirical study to test the relation between EQCR hours and auditor changes.